Development of Interactive Learning Media on Coordination System Topics Using Adobe Flash CS8 for Class XI Students - Akmal, Muhammad (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2019)
This research aims to create interactive learning media that can help class XI high school students understand Coordination system material, which students at SMAN 1 Muaro Jambi found difficult to understand based on observation results. The development model used is the ADDIE model which consists of the stages of Analysis, Design, Development, Implementation and Evaluation. The data collected consists of qualitative and quantitative types. Qualitative data was obtained from validator questionnaires, while quantitative data was obtained from student and teacher perception questionnaires. After validation by media experts 2 times and material experts 3 times, the learning media developed received a very good final score. Trials were carried out on small groups (8 students) and large groups (20 students) at SMAN 8 Muaro Jambi, which resulted in very good scores. Biology subject teachers' perceptions also show a very good assessment of this learning media. Thus, Interactive Learning Media on the subject of Coordination Systems Using Adobe Flash CS8 for Class This media can also be an alternative for students in independent learning. This research can be a reference in developing relevant learning media products in the future.